Clinical/nutritional parameters and gestational history of mothers of children living with cleft lip and palate (Research, Society and Development, 2024)
Cleft lip and palate (CLP) originate from different stages of embryonic-fetal development and is associated with a multifactorial etiology, with risk factors in the Genetic-Environmental-Social context. In this study, we focused on the analysis of mothers of children with CLP – attended at a reference dental clinic in southern Minas Gerais, Brazil. Data obtained through a semi-structured questionnaire revealed a sample of 73 patients with CLP, predominantly aged 1-5 years (43.83%, CI 95% 32.41; 55.91), white (72.60%, CI 95% 60.71; 82.08), with maternal age among the 73 mothers interviewed, mostly between 20-35 years old (69.86%, CI 95% 57.85; 79.76), and having completed high school. In the medical/nutritional history, there was no significant relationship with comorbidities (Diabetes Mellitus, Systemic Arterial Hypertension and Dyslipidemia), but through the BMI, it was possible to report the presence of varying degrees of nutritional dysfunctions [malnutrition, overweight and obesity levels]. Most mothers had prenatal care (97.26%, CI 95% 87.85; 100) and, during pregnancy, a considerable frequency of alcohol use, tobacco and illicit drugs was observed, and 36.99% (CI 95% 8.99; 43.06) of the studied mothers had an infection during pregnancy and/or used medication with teratogenic risks. Of note, 72% of mothers underwent through stressful situations during pregnancy, which is a risk factor in the etiology of FLP. As a factor in preventing CLP, most respondents used folic acid during pregnancy. The importance of prospecting risk factors for CLP in the prenatal period and monitoring mothers and newborns are highlighted, due to the multifactorial context of the disease.